Understanding the Energy Sector Reform in Pakistan and Its Implications - Ashar Awan; Faik Bilgili; Dil Bahadur Rahut (Asian Development Bank Institute (ADBI), 2024)
The power sector of Pakistan has undergone numerous reforms, in this context the present study examines the impact of these reforms on efficacy and sustainability. The literature on power sector reforms in developing countries is extensive and diverse, covering various aspects and dimensions of the reform process and its outcomes. However, there is a lack of comprehensive and systematic studies in the case of Pakistan dealing with extensive range of reforms over a long period. This study fills this gap by providing a comprehensive and systematic evaluation of Pakistan's power sector reforms. The findings show that after the reforms, installed generation capacity has increased and the energy mix has shifted to expensive fossil fuels, however, there has been no substantial reduction in transmission and distribution loses. Nominal electricity tariffs increased the least for residential sector creating cross-sector subsidies at the cost of industrial sector. In addition, electricity consumption by residential sector increased substantially, while the commercial, agriculture and industrial sectors shows no significant increase in electricity consumption. The GDP share of the manufacturing and industrial sector declined. The study recommends tariff restructuring to protect poor households and ensuring the industrial sector remains competitive.
Keywords: L94; P11; Q01; L51; Q40; 330; power sector; reforms; Pakistan; energy poverty; SDG 7